Rediscovery of Hyalinobatrachium chirripoi (Anura: Centrolenidae) in southeastern Costa Rica - Kubicki, Brian (2004)
The Suretka glass frog, Hyalinobatrachium chirripoi, has been recently rediscovered in the south-eastern region of Costa Rica. This species was last reported in Costa Rica in the 1950’s. H. chirripoi is distin-guished from H. colymbiphyllum, which appears to be its most closely Costa Rican related taxon, by havingextensive webbing between fingers II-III.